2011
DOI: 10.1002/alr.20075
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intraoperative saline irrigations on bacterial load within the maxillary sinus

Abstract: Background Saline irrigations are routinely employed during endoscopic sinus surgery to remove mucous and debris from the sinus cavities. What is unknown is whether this results in a quantitative reduction in pathologic bacteria within the sinus mucosa. The objectives of this study were to quantify the amount of 5 different bacteria (Staphylococcus aureus, Haemophilus influenzae, Pseudomonas aeruginosa, coagulase-negative Staphylococcus (CNS), and Streptococcus pneumoniae) within the maxillary sinus and to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Postoperatively, patients were routinely placed on sinus irrigations and a 2‐week course of oral antibiotics (amoxicillin‐clavulanate, or clarithromycin if penicillin‐allergic). Bacterial load was hypothesized to be the lowest after treatment (FESS with irrigation at completion of surgery, followed by 2 weeks of postoperative antibiotics and saline rinses), and then bacterial repopulation was expected to subsequently occur in the following weeks. As such, we compared microbiota present at the time of surgery, 2 weeks postoperatively, and 6 weeks postoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…Postoperatively, patients were routinely placed on sinus irrigations and a 2‐week course of oral antibiotics (amoxicillin‐clavulanate, or clarithromycin if penicillin‐allergic). Bacterial load was hypothesized to be the lowest after treatment (FESS with irrigation at completion of surgery, followed by 2 weeks of postoperative antibiotics and saline rinses), and then bacterial repopulation was expected to subsequently occur in the following weeks. As such, we compared microbiota present at the time of surgery, 2 weeks postoperatively, and 6 weeks postoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Seiberling et al verified that intraoperative saline irrigation can significantly reduce the amount of potentially pathogenic bacteria within diseased sinus mucosa. 14…”
Section: Discussionmentioning
confidence: 99%
“…We have previously established that intraoperative saline irrigations are effective in reducing the load of pathogenic bacteria within the maxillary sinus . Although it is unclear whether this will have a clinical impact, it is assumed that healing may be improved due to the decrease in bacterial load within the sinus mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…There is a gap in knowledge regarding whether intraoperative rinses of mupirocin are effective in reducing the load of S. aureus in patients with CRS. In a previous study we reported that intraoperative saline rinses effectively reduce bacterial load within the treated sinus . In this study, our goal is to determine: (1) if mupirocin rinses reduce the bacterial load of S. aureus within the maxillary sinus; and (2) if the antibiotic rinse is more effective than saline irrigations alone.…”
mentioning
confidence: 99%